The Temple in early Christianity: experiencing the sacred - Regev, Eyal (The Anchor Yale Bible reference library, 2019)
Jesus: "Cleansing," trial, and Last Supper -- Paul's letters: Temple imagery as religious identity -- Mark: criticism or rejection? -- Q and Matthew: the Sacred Temple -- Luke-Acts: living and dying with the Temple -- The Gospel of John: Temple and Christology -- The Book of Revelation: the alternative Temple -- Hebrews: the new heavenly temple cult based on the old one -- Relating to Judaism, experiencing the sacred -- Concluding thoughts.